The Dual Role of Low-Density Lipoprotein Receptor-Related Protein 1 in Atherosclerosis - Chen, Jiefang; Su, Ying; Pi, Shulan; Hu, Bo; Mao, Ling (Frontiers in Cardiovascular Medicine, 2021)
Low-density lipoprotein receptor–related protein-1 (LRP1) is a large endocytic and signaling receptor belonging to the LDL receptor (LDLR) gene family and that is widely expressed in several tissues. LRP1 comprises a large extracellular domain (ECD; 515 kDa, α chain) and a small intracellular domain (ICD; 85 kDa, β chain). The deletion of LRP1 leads to embryonic lethality in mice, revealing a crucial but yet undefined role in embryogenesis and development. LRP1 has been postulated to participate in numerous diverse physiological and pathological processes ranging from plasma lipoprotein homeostasis, atherosclerosis, tumor evolution, and fibrinolysis to neuronal regeneration and survival. Many studies using cultured cells and in vivo animal models have revealed the important roles of LRP1 in vascular remodeling, foam cell biology, inflammation and atherosclerosis. However, its role in atherosclerosis remains controversial. LRP1 not only participates in the removal of atherogenic lipoproteins and proatherogenic ligands in the liver but also mediates the uptake of aggregated LDL to promote the formation of macrophage- and vascular smooth muscle cell (VSMC)-derived foam cells, which causes a prothrombotic transformation of the vascular wall. The dual and opposing roles of LRP1 may also represent an interesting target for atherosclerosis therapeutics. This review highlights the influence of LRP1 during atherosclerosis development, focusing on its dual role in vascular cells and immune cells.